Bill 1. : Fig 23: Euryale (Susan Hampshire) is the Gorgon in Malpertuis. Note how her hair is curled to resemble snakes and her eyes are fixed with a petrifying stare. From the book Unreal reality of Harry Kümel, shot by S Po. - Peeters, Julie; Narbutaité, Elena (Amsterdam : ROMA Publications, 2017)
Lempert, Jochen ; Alexi-Meskhishvili, Ketuta ; Mater, Katja ; Narbutaité, Elena ; Nashashibi, Rosalind ; Suter, Vivian ; Ou, Arthur ; Ponik, Scott ; Putnam, Adam ; Schwartz, Johannes ; Seskus, Algirdas ; Van Deursen, Linda
boek